The paradox of training metrics - Sinha, Anamika; Varkkey, Biju (London : Indian Institute of Management, Ahmedabad, 2017)
In the face of increased competition, Ratnamani Metal and Tubes Ltd (RMTL) began a new training program for its employees hoping to professionalize its workforce. The company found that the return on training investment was high yet the company continued to have high rates of attrition. In exit interviews, employees often cited opportunity for work elsewhere as the reason for leaving RTML. The increase in training meant that RTM's employees became more desirable to competitors.
Originally published in : Sinha, A., & Varkkey, B. (2017). The Paradox of Training Metrics. HRM0236. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Ratnamani Metal and Tubes Ltd. -- Case studies; Employees -- Training of -- Evaluation -- Case studies; Labor turnover -- Case studies